Stem Cell-Based Therapies for Liver Diseases: State of the Art and New Perspectives - Anna Chiara Piscaglia; Mariachiara Campanale; Antonio Gasbarrini; Giovanni Gasbarrini (Stem Cells International)
Millions of patients worldwide suffer from end-stage liver pathologies, whose only curative therapy is liver transplantation (OLT). Given the donor organ shortage, alternatives to OLT have been evaluated, including cell therapies. Hepatocyte transplantation has been attempted to cure metabolic liver disorders and end-stage liver diseases. The evaluation of its efficacy is complicated by the shortage of human hepatocytes and their difficult expansion and cryopreservation. Recent advances in cell biology have led to the concept of “regenerative medicine”, based on the therapeutic potential of stem cells (SCs). Different types of SCs are theoretically eligible for liver cell replacement. These include embryonic and fetal SCs, induced pluripotent cells, annex SCs, endogenous liver SCs, and extrahepatic adult SCs. Aim of this paper is to critically analyze the possible sources of SCs suitable for liver repopulation and the results of the clinical trials that have been published until now.